2021
DOI: 10.3390/ijms22020865
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Effect of Air-Polishing Treatments and Their Influence on Human Dental Pulp Stem Cells Seeded on Titanium Disks

Abstract: Dental implants are one of the most frequently used treatment options for tooth replacement, and titanium is the metal of choice due to its demonstrated superiority in resisting corrosion, lack of allergic reactions and mechanical strength. Surface roughness of titanium implants favors the osseointegration process; nevertheless, its topography may provide a suitable substrate for bacterial biofilm deposition, causing peri-implantitis and leading to implant failure. Subgingival prophylaxis treatments with clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…Glycine powder air polishing resulted in a significantly higher reduction in plaque around implants [7,11], and effective in reducing peri-implant inflammation [25]. In vitro studies showed that also tagatose powders could have cleaning potential with great results [21]. In addition, the combination of glycine and taurolidine could enhance effectiveness of plaque-removing procedures [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycine powder air polishing resulted in a significantly higher reduction in plaque around implants [7,11], and effective in reducing peri-implant inflammation [25]. In vitro studies showed that also tagatose powders could have cleaning potential with great results [21]. In addition, the combination of glycine and taurolidine could enhance effectiveness of plaque-removing procedures [31].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 40 additional articles were excluded after full text review and application of the eligibility criteria. The final selection consisted of 19 articles [6,7,11,13,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Bibliographic Search and Study Selectionmentioning
confidence: 99%
“…PEDOT-hDPSCs samples were mounted with FluoroMount anti-fading medium (Thermo Fisher Scientific, Waltham, MA, United States) on glass cover slides. Cell proliferation was evaluated by counting the DAPI-labelled nuclei on five randomly selected fields measuring 2.5 × 10 5 μm 2 on three samples for each experimental group by a blind operator and acquired by using a Nikon A1 confocal fluorescence microscope (Nikon, Tokyo, Japan), as formerly described ( Di Tinco et al, 2021b ). hDPSCs cultured on plastic culture plates were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were undergoing extractions as a part of routine orthodontic or periodontal therapy. The sample size determination was conducted based on previous studies that have performed similar studies on stem cells [13,14]. However, sample size is not a critical determinant in stem cell experiments as stem cells have uniform properties and are cultured through many passages for the tests.…”
Section: Sample Size Determination and Sample Collectionmentioning
confidence: 99%